CD28 Superagonist-Mediated Boost of Regulatory T Cells Increases Thrombo-Inflammation and Ischemic Neurodegeneration during the Acute Phase of Experimental Stroke. Issue 1 (January 2015) - Schuhmann, Michael K; Kraft, Peter; Stoll, Guido; Lorenz, Kristina; Meuth, Sven G; Wiendl, Heinz; Nieswandt, Bernhard; Sparwasser, Tim; Beyersdorf, Niklas; Kerkau, Thomas; Kleinschnitz, Christoph
While the detrimental role of non-regulatory T cells in ischemic stroke is meanwhile unequivocally recognized, there are controversies about the properties of regulatory T cells (Treg ). The aim of this study was to elucidate the role of Treg by applying superagonistic anti-CD28 antibody expansion of Treg . Stroke outcome, thrombus formation, and brain-infiltrating cells were determined on day 1 after transient middle cerebral artery occlusion. Antibody-mediated expansion of Treg enhanced stroke size and worsened functional outcome. Mechanistically, Treg increased thrombus formation in the cerebral microvasculature. These findings confirm that Treg promote thrombo-inflammatory lesion growth during the acute stage of ischemic stroke.